2021
DOI: 10.1016/j.esmoop.2021.100107
|View full text |Cite
|
Sign up to set email alerts
|

High body mass index and pre-existing autoimmune disease are associated with an increased risk of immune-related adverse events in cancer patients treated with PD-(L)1 inhibitors across different solid tumors

Abstract: Available online xxxBackground: Treatment with anti-PD-(L)1 antibodies, approved for several oncology indications, can lead to immunerelated adverse events (irAEs). We aimed to investigate risk factors associated with an increased reporting of irAEs in patients treated with PD-(L)1 inhibitors approved for solid tumor indications. Patients and methods: A retrospective review was performed of individual data from patients in phase II/III registrational studies for PD-(L)1 inhibitors in solid tumors. Data on base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11] Studies on the BMI-safety association using clinical trial data have shown heterogeneous results, with some studies indicating no association 7 and others suggesting an increased risk. 20,22 Similarly, meta-analyses 12,21 have demonstrated heterogeneous results. Our study analyzed primary trial data in which irAEs were uniformly defined across the trials and included 2746 patients receiving nivolumab monotherapy and 1026 patients treated with combination therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6][7][8][9][10][11] Studies on the BMI-safety association using clinical trial data have shown heterogeneous results, with some studies indicating no association 7 and others suggesting an increased risk. 20,22 Similarly, meta-analyses 12,21 have demonstrated heterogeneous results. Our study analyzed primary trial data in which irAEs were uniformly defined across the trials and included 2746 patients receiving nivolumab monotherapy and 1026 patients treated with combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity, a risk factor for developing many tumor types, has paradoxically been associated with improved outcomes for patients receiving ICIs . Studies on the BMI-safety association using clinical trial data have shown heterogeneous results, with some studies indicating no association and others suggesting an increased risk . Similarly, meta-analyses have demonstrated heterogeneous results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that a higher BMI increases the risk of irAEs in patients with NSCLC, melanoma, renal cell carcinoma, urothelial carcinoma, and squamous cell carcinoma of the head and neck, suggesting that BMI may contribute to irAEs ( Cortellini et al, 2020 ; Gülave et al, 2021 ; Leiter et al, 2021 ). In our study of patients with primary liver cancer, we observed that patients with irAEs had a higher BMI compared to non-irAE patients, with overweight patients experiencing an increased incidence of irAEs.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of solid tumors, high serum albumin levels were discovered to be a risk factor for irAEs (24). Another retrospective analysis in the field of pan-cancer found that patients with high BMI had a higher probability of experiencing irAEs (25). Patients who experienced severe immune-related pneumonitis had a significant morbidity and mortality rate, according to a retrospective investigation by Suresh et al in NSCLC, but no additional research into predictors was done (26).…”
Section: Discussionmentioning
confidence: 99%